Oxygen consumption of Litopenaeus vannamei juveniles in heterotrophic medium with zero water exchange - Vinatea, Luis; Galvez, Alfredo Oliveira; Venero, Jesus; Leffler, John; Browdy, Craig (Pesquisa Agropecuaria Brasileira, 2010)
This work aimed at determining the dissolved oxygen consumption rate of Litopenaeus vannamei juveniles maintained in a microbial biofloc raceway system at high density with no aeration. Three 4 L bottles were filled for each treatment, sealed hermetically, and placed in an enclosed greenhouse raceway system. Four shrimp (13.2±1.42 g) were assigned to two sets of the bottles, which underwent the following treatments: light conditions with no shrimp; dark conditions with no shrimp; light conditions with shrimp; and dark conditions with shrimp. Dissolved oxygen content was measured every 10 min for 30 min. A quadratic behavior was observed in dissolved oxygen concentration over time. Significant differences for oxigen consumption were observed only at 10 and 20 min between shrimp maintained in the dark and those under light conditions. At 10 min, a higher value was observed in shrimp maintained under light, and at 20 min, in the dark. Significant differences between 10 and 20 min and between 10 and 30 min were observed when oxygen consumption was analyzed over time in the presence of light. Under dark conditions there were significant differences only between 20 and 30 min. Lethal oxygen concentration (0.65 mg L-1) would be reached in less than one hour either under light or dark conditions with no aeration.